Cortical gray matter myelin cuts energy cost of spike propagation without increasing conduction velocity - Oron Kotler; Yana Khrapunsky; Israel Melamed; Elior Peles; William N. Ross; Ilya Fleidervish (Proceedings of the National Academy of Sciences, 2026)
Myelin is a hallmark of vertebrate nervous systems, yet its roles in central axons remain elusive. Using optical and electrical recordings from thin axons of Layer 5 pyramidal neurons in murine cortical gray matter of animals of either sex, and computational modeling, we argue that myelination halves the metabolic cost of spike propagation with little effect on conduction velocity. Modeling indicates that, although greater speed and energy efficiency are theoretically possible, these would compromise repolarization and the function of internodal voltage-gated channels and pumps. We further suggest that, in contrast to peripheral axons, cortical myelin segregates current flow within periaxonal nanodomains. High-frequency currents, key for the rising phase of the action potential, traverse the myelin sheath to facilitate propagation, whereas low-frequency currents leak through paranodal junctions, supporting repolarization and ion homeostasis. These results suggest that cortical myelin adopts a structural trade-off that favors metabolic efficiency and ionic homeostasis over maximal velocity.